ANALISIS SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS PADA DINAS PENDAPATAN DAERAH KABUPATEN BERAU - NURHIDAYATI, SAFITRI (ACCOUNTING STUDY PROGRAM, STIE MUHAMMADIYAH TANJUNG REDEB, 2017)
Analysis of Accounting Information System of Cash Receipts at Regional Revenue Office of Berau District. The purpose of this study is to know clearly about the implementation of accounting information system cash receipts in the District Revenue Office of Berau , the method of analysis used qualitative descriptive analysis method.        Based on the results of the analysis can be concluded that rejection of  the hypothesis in this study because it is evident that the accounting information system cash receipts at the Regional Revenue Office of Berau District is in accordance with Regulation of Government Number 13 of 2006. There are advantages in the implementation of accounting information system cash receipts, namely: The order is printed and the document has been well archived by the authorized officer.       The use of accounting note is suitable conformity with the existing accounting information standard, which contains a summary of transactions that occurred during a certain period, Therefore, to facilitate the discovery of non-conformity of account balances in the accountancy.